The Elixir of Visiting: A Qualitative Study on the Experiences of Conscious Mechanically Ventilated Patients in Intensive Care Units Regarding Visiting Family Members - Fatemeh Hajiabadi; Abbas Heydari; Zahra Sadat Manzari (Mashhad University of Medical Sciences, 2017)
Background: Visiting family members is one of the basic human needs; however, there is contradictory evidence about the advantages and disadvantages of the existing visiting systems.  Therefore, the investigation of patients' preferences for the visiting strategies, and achievement of their authentic experiences can significantly contribute to decision-making about the type of acceptable and approved policies in this domain. Aim: The aim of this study was to explain the experiences of conscious patients undergoing mechanical ventilation in Intensive Care Units regarding their visits with their family members. Method: This qualitative study was conducted on 15 conscious mechanically ventilated patients admitted to the Intensive Care Unit in Iran in 2017. The data were collected using semi-structured interviews and observations. The sampling was performed through purposive sampling technique, which was continued until data saturation to select the individuals with rich experiences about the subject under investigation. The data were analyzed through the conventional type of qualitative content analysis. Results: Out of the initial 385 codes, 11 subthemes and 5 main themes were extracted during the analysis process, all of which were placed under the general concept of "the elixir of visiting". The five main themes included visiting as a healing agent, visiting as an agent for the enhancement of perceived support, visiting as an agent for gaining hope, visiting as the patient's urgent need, and preference for planed visiting. Implications for Practice: The results of the present study showed that visiting was like an elixir for the conscious patients undergoing mechanical ventilation in the Intensive Care Units. This practice could allay lots of their pains and lead to numerous valuable effects, such as elimination of loneliness and sadness, increased hope for survival and recovery, and enhancement of a sense of support. Therefore, nursing authorities and managers are required to take steps in terms of redefining visiting rules and regulations in line with patients' preferences, and thereby move towards the promotion of patient care.